High concentrations of the melatonin metabolite, N-1-acetyl-N (2)-formyl-5-methoxykynuramine, in cerebrospinal fluid of patients with meningitis: a possible immunomodulatory mechanism - Silva, S. O.; Ximenes, Valdecir Farias [UNESP]; Livramento, J. A.; Catalani, L. H.; Campa, A. (Blackwell Publishing, 2005)
We evaluated the presence of the melatonin metabolite N-1-acetyl-N-2-formyl-5-methoxykynuramine (AFMK), in cerebrospinal fluid (CSF) of patients with viral meningitis (n = 20) and control samples (n = 8) and correlate AFMK levels with inflammatory markers such as cellularity, protein, tumor necrosis factor (TNF)-alpha, interleukin (IL)-8 and IL-1 beta levels. A portion of the CSF was extracted with dichloromethane (1:5) and analyzed by high-performance liquid chromatography (HPLC) under standardized conditions for AFMK. AFMK was detected in 16 of 20 CSF samples of patients with viral meningitis; the concentration of AFMK was found to be above the quantification limit (50 nmol/L) in six of these samples. AFMK was not detected in any of the eight control samples. The samples were classified into groups according to AFMK levels: undetectable (< 10 nmol/L, group I), detectable but below the quantification limit (< 50 nmol/L, group II), and quantified (> 50 nmol/L, group III). Group II presented the highest levels of proteins and IL-8, whereas group III showed the lowest levels of the inflammatory parameters. This study supports our hypothesis that inflammation favors the formation of AFMK and that this compound has immunomodulatory activity in vivo.
Keywords: cerebrospinal fluid; cytokines; inflammation; kynurenines; melatonin; N-1-acetyl-N-2-formyl-5-methoxykynuramine